2011
DOI: 10.1249/mss.0b013e318206c66e
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Physical Activity and Physical and Mental Health- A HUNT 3 Study

Abstract: The study suggests that exercising at any level is associated with better physical and mental health in both genders compared with no exercise, particularly among the older individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
54
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 26 publications
7
54
0
1
Order By: Relevance
“…Engaging in and maintaining an active lifestyle receives special attention considering the advancing demographic changes in some societies, since active individuals report better physical and mental health (Bertheussen et al, 2011). In line with Salthouse (1991), some studies in the context of health behavior research provided support for his argument that chronological age alone might not be a suitable predictor to explain age-related effects in health behaviors, as long as other age concepts can also contribute to the explanation of age-related phenomena (e.g., decline in physical activity; cf.…”
Section: Introductionmentioning
confidence: 99%
“…Engaging in and maintaining an active lifestyle receives special attention considering the advancing demographic changes in some societies, since active individuals report better physical and mental health (Bertheussen et al, 2011). In line with Salthouse (1991), some studies in the context of health behavior research provided support for his argument that chronological age alone might not be a suitable predictor to explain age-related effects in health behaviors, as long as other age concepts can also contribute to the explanation of age-related phenomena (e.g., decline in physical activity; cf.…”
Section: Introductionmentioning
confidence: 99%
“…However, some studies fail to show that the intervention increases physical activity (e.g., Jago et al, 2011), and for most biometric health outcomes, the evidence is less conclusive if they are studied at all (Proper et al, 2002;Proper et al, 2005; for a disagreeing perspective, see WHO, 2009). Empirical studies in this area are generally difficult to interpret because they often lack randomization and longitudinal designs (Dishman et al, 1998;Proper, 2008), though some of the more recent studies incorporate these features and have more positive results (e.g., Bertheussen et al, 2011). No previous studies test workplace interventions involving walking while working.…”
Section: Conceptual Framework and Relevant Literaturementioning
confidence: 99%
“…On the basis of this hypothesis and the fact that greater physical activity is positively (certainly not negatively) related to health (Bertheussen, 2011), we expect WWW to have a positive effect on health outcomes. However, the effects may take a long time to materialize because of the limited intensity of the physical effort associated with slow walking; some biometric measures may respond faster than others.…”
Section: H1 the Introduction Of Www Improves Physical Activitymentioning
confidence: 99%
“…While cheap and relatively easy to administer [6,7], physical activity questionnaires are incapable of objectively quantifying physical activity and, due to self-report, are inherently unreliable. One study in 2011 found a 40% difference between participants who met recommended daily activity levels when daily activity levels were determined through self-reported questionnaire versus direct researcher observation [8]. Objective methods are necessary to quantify physical activity in order to assess its impacts on health.…”
mentioning
confidence: 99%